1992
DOI: 10.1161/01.cir.85.1.205
|View full text |Cite
|
Sign up to set email alerts
|

Are aortic aneurysms caused by atherosclerosis?

Abstract: BACKGROUND The emerging controversy concerning the causal role of atherosclerosis in the development of aortic aneurysms was examined using the accumulated clinical and autopsy data obtained during a 20-year follow-up of a cohort of more than 8,000 men of Japanese ancestry in Hawaii. METHODS AND RESULTS Analyses of 174 clinical incident events indicated that there were two types of aneurysmal disease, 151 aortic aneurysms and 23 aortic dissections. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
177
1
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(187 citation statements)
references
References 25 publications
6
177
1
3
Order By: Relevance
“…The process of development from atherosclerosis to rupture of aortic aneurysms may be longer and more complicated than that from atherosclerosis to infarction of coronary arteries. Epidemiologic studies have also demonstrated a 2 to 8-fold increased risk of aortic aneurysms in heavy smokers compared to nonsmokers (Hirayama 1992;Reed et al 1992). However, in Japan the sharply increasing mortality rates of aortic aneurysms were inconsistent with a declining trend for the proportion of smokers during the same period (Ministry of Health and Welfare 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The process of development from atherosclerosis to rupture of aortic aneurysms may be longer and more complicated than that from atherosclerosis to infarction of coronary arteries. Epidemiologic studies have also demonstrated a 2 to 8-fold increased risk of aortic aneurysms in heavy smokers compared to nonsmokers (Hirayama 1992;Reed et al 1992). However, in Japan the sharply increasing mortality rates of aortic aneurysms were inconsistent with a declining trend for the proportion of smokers during the same period (Ministry of Health and Welfare 1993).…”
Section: Discussionmentioning
confidence: 99%
“…30 -32 Leukocyte recruitment and expression of pro-inflammatory cytokines characterize early atherogenesis. 1 AAA typically arise in the setting of severe atherosclerosis, 33 and several studies suggest that the aneurysmal disease may progress from occlusive disease. 34 Because AAA frequently coexist with generalized atherosclerosis, they are frequently termed "atherosclerotic aneurysms."…”
mentioning
confidence: 99%
“…In these disorders, a chronic inflammatory infiltrate of the aortic medial and adventitial vasa vasorum is present, with many lymphocytes, macrophages and multinucleated giant cells (6,(8)(9)(10). Giant cell arteritis patients have 2.4 times the risk of developing aortic aneurysms compared with the general population (3,11,12).…”
Section: Discussionmentioning
confidence: 99%